Answer

Verified

483.6k+ views

Hint: The given expression is $x - iy = \sqrt {\dfrac{{a - ib}}{{c - id}}} $, use the concept of taking complex conjugate to this equation keeping one thing in mind that complex conjugate effect only the iota terms and not any real term. This will help you reach the proof in this question.

The given expression is $x - iy = \sqrt {\dfrac{{a - ib}}{{c - id}}} $……………………….. (1)

We need to prove that ${\left( {{x^2} + {y^2}} \right)^2} = \dfrac{{{a^2} + {b^2}}}{{{c^2} + {d^2}}}$……………… (2)

Taking complex conjugate both the sides of equation (1) we get,

$\overline {x - iy} = \overline {\sqrt {\dfrac{{a - ib}}{{c - id}}} } $………………… (3)

Using the property of conjugate $\overline {\left( {a + ib} \right)} = \left( {\overline a + \overline {ib} } \right)$ in equation (3) we get,

$\overline x - \overline {iy} = \sqrt {\dfrac{{\overline a - \overline {ib} }}{{\overline c - \overline {id} }}} $……………… (4)

Now using the property that $\overline x = x{\text{ and }}\overline i = - i$in equation (4) we get,

$x + iy = \sqrt {\dfrac{{a + ib}}{{c + id}}} $……………………… (5)

Now let’s multiply equation (1) and equation (5) we get,

$(x - iy)(x + iy) = \sqrt {\dfrac{{a + ib}}{{c + id}}} \times \sqrt {\dfrac{{a - ib}}{{c - id}}} $

\[ \Rightarrow (x - iy)(x + iy) = \sqrt {\dfrac{{a + ib}}{{c + id}} \times \dfrac{{a - ib}}{{c - id}}} \]……………………….. (6)

Now using the identity $\left( {a - b} \right)\left( {a + b} \right) = {a^2} - {b^2}$ in equation (6) we get,

$ \Rightarrow {x^2} - {i^2}{y^2} = \sqrt {\dfrac{{{a^2} - {i^2}{b^2}}}{{{c^2} - {i^2}{d^2}}}} $

Using ${i^2} = - 1$ we get

$ \Rightarrow {x^2} + {y^2} = \sqrt {\dfrac{{{a^2} + {b^2}}}{{{c^2} + {d^2}}}} $

Squaring both sides,

${\left( {{x^2} + {y^2}} \right)^2} = \dfrac{{{a^2} + {b^2}}}{{{c^2} + {d^2}}}$

Hence proved

Note: Whenever we face such types of problems the key concept is based upon taking complex conjugate and using the various properties of complex conjugate, some of them are being mentioned above while performing the solution. This will help you get on the right track to reach the proof.

The given expression is $x - iy = \sqrt {\dfrac{{a - ib}}{{c - id}}} $……………………….. (1)

We need to prove that ${\left( {{x^2} + {y^2}} \right)^2} = \dfrac{{{a^2} + {b^2}}}{{{c^2} + {d^2}}}$……………… (2)

Taking complex conjugate both the sides of equation (1) we get,

$\overline {x - iy} = \overline {\sqrt {\dfrac{{a - ib}}{{c - id}}} } $………………… (3)

Using the property of conjugate $\overline {\left( {a + ib} \right)} = \left( {\overline a + \overline {ib} } \right)$ in equation (3) we get,

$\overline x - \overline {iy} = \sqrt {\dfrac{{\overline a - \overline {ib} }}{{\overline c - \overline {id} }}} $……………… (4)

Now using the property that $\overline x = x{\text{ and }}\overline i = - i$in equation (4) we get,

$x + iy = \sqrt {\dfrac{{a + ib}}{{c + id}}} $……………………… (5)

Now let’s multiply equation (1) and equation (5) we get,

$(x - iy)(x + iy) = \sqrt {\dfrac{{a + ib}}{{c + id}}} \times \sqrt {\dfrac{{a - ib}}{{c - id}}} $

\[ \Rightarrow (x - iy)(x + iy) = \sqrt {\dfrac{{a + ib}}{{c + id}} \times \dfrac{{a - ib}}{{c - id}}} \]……………………….. (6)

Now using the identity $\left( {a - b} \right)\left( {a + b} \right) = {a^2} - {b^2}$ in equation (6) we get,

$ \Rightarrow {x^2} - {i^2}{y^2} = \sqrt {\dfrac{{{a^2} - {i^2}{b^2}}}{{{c^2} - {i^2}{d^2}}}} $

Using ${i^2} = - 1$ we get

$ \Rightarrow {x^2} + {y^2} = \sqrt {\dfrac{{{a^2} + {b^2}}}{{{c^2} + {d^2}}}} $

Squaring both sides,

${\left( {{x^2} + {y^2}} \right)^2} = \dfrac{{{a^2} + {b^2}}}{{{c^2} + {d^2}}}$

Hence proved

Note: Whenever we face such types of problems the key concept is based upon taking complex conjugate and using the various properties of complex conjugate, some of them are being mentioned above while performing the solution. This will help you get on the right track to reach the proof.

Recently Updated Pages

what is the correct chronological order of the following class 10 social science CBSE

Which of the following was not the actual cause for class 10 social science CBSE

Which of the following statements is not correct A class 10 social science CBSE

Which of the following leaders was not present in the class 10 social science CBSE

Garampani Sanctuary is located at A Diphu Assam B Gangtok class 10 social science CBSE

Which one of the following places is not covered by class 10 social science CBSE

Trending doubts

How do you graph the function fx 4x class 9 maths CBSE

Which are the Top 10 Largest Countries of the World?

The Equation xxx + 2 is Satisfied when x is Equal to Class 10 Maths

Difference Between Plant Cell and Animal Cell

Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE

1 ton equals to A 100 kg B 1000 kg C 10 kg D 10000 class 11 physics CBSE

In Indian rupees 1 trillion is equal to how many c class 8 maths CBSE

The largest tea producing country in the world is A class 10 social science CBSE

One Metric ton is equal to kg A 10000 B 1000 C 100 class 11 physics CBSE